Mentoring millennials in surgical education. Issue 4 (August 2019) - Louie, Michelle; Moulder, Janelle K.; Wright, Kelly; Siedhoff, Matthew
Abstract : Purpose of review: We seek to define the Millennial generation and identify strengths that can be employed to improve medical and surgical education and career development. We outline how generational traits can be incorporated into adult learning theory, offer suggestions for modernizing traditional teaching and mentorship models, and discuss why Millennials are ideally positioned to succeed in 21st century medicine. Recent findings: Millennials (born ∼1981 to 1996) have several consistently identified traits that should be considered when teaching trainees and mentoring junior faculty. Millennials are technologically savvy, accustomed to accessing and assimilating large amounts of information quickly, using the electronic medical record with ease, and learning from a variety of media sources. They learn better with alternatives to traditional lectures, and respond well when given discrete goals, encouragement, and direct feedback early and often. Millennials prefer team-based learning and a flat hierarchy. Millennials are socially responsible, culturally diverse, and strive to promote diversity and work-life integration. Summary: Although the individuals that make up the Millennial generation may not encompass each attribute associated with this cohort, collectively, this generation of physicians is positioned to usher medicine into a new era.